Influence of Environmental Degradation and Economic Growth on CO2 Emissions: Evidence from Developing Countries - Khan, Rabnawaz; Kong, YuSheng; Xinxin, Jin (Asian Journal of Economics and Empirical Research, 2020)
China is working to revive the ancient on the Silk road trade routes from Asia to Europe and promote the corporation of energy production with trade under its transactional megaproject the Belt and Road (BRI) initiative. We investigate the relationship between energy consumption and economic growth of regions in this paper along with BRI using panel data for 55 countries during the period of 1970-2015. By assessing Vector Error Correction Model (VECM), fully changed Ordinary Least Squares (FMOLS) and dynamic Ordinary Least Squares regression (DOLS) with first generation test. The statistical finding there is evidence from long-run bidirectional causalities among CO2 emissions, energy use per capita, GDP per capita, manufacturing industries and fossil fuel energy consumption. Hence, there is unidirectional short-run causality running from GDP to renewable energy in South Asia BRI listed countries and bidirectional causality between consumption of energy and GDP per capita in the long run East Asia (Australia, Brunei, Indonesia, Malaysia, Myanmar, Vietnam), Europe & Central Asia (Azerbaijan, Kazakhstan. Russian, Turkmenistan, Uzbekistan) and Middle East & North Africa (Bahrain. Egypt, Iran, Iraq, Kuwait, Oman, Qatar, UAE, Yemen). The results confirm the renewable energy and fossil energy consumption and manufacturing industries. These outcomes suggest significant provision in the economies and trade of China with different countries in the Belt and Road regions.